P17 | INTERMITTENT FASTING AND FUCOIDAN ADMINISTRATION AMELIORATE THE EFFECT OF TYPE 2 DIABETES ON ENTERIC NERVOUS SYSTEM IN RATS (European Journal of Histochemistry)
Type 2 diabetes mellitus (T2DM) is a chronic inflammatory disorder that affects glucose metabolism, the enteric nervous system (ENS), and the gut-brain axis1-3. The study investigates the effects of intermittent fasting (IF) and fucoidan (F), a sulfated polysaccharide with antioxidant properties, on oxidative stress (OS) and neuroinflammation in a streptozotocin (STZ)/nicotinamide (NA)-induced rat T2DM model. The study involved 40 adult male Sprague-Dawley rats divided into six groups: Control, T2DM, T2DM+IF (16-h fasting for 30 days), T2DM+F (100 mg/kg/day, oral), and T2DM+IF+F. The results showed that hyperglycemia significantly decreased in all treatment groups, while diabetes reduced body weight. Neuronal density, goblet cell count, and villus height were reduced in diabetic rats, while iNOS and occludin expression levels were suppressed. Elevated levels of luminol, lucigenin, MDA, and MPO, and reduced GSH in diabetic rats were significantly reversed in treated groups. These findings suggest that IF and fucoidan synergistically mitigate OS, enhance mucosal integrity, and reduce neuroinflammation, supporting their potential as adjunctive strategies for T2DM management.